A circularly polarized folded reflectarray antenna using a polarization-sensitive linear-to-circular polarization converter - Liu, Shuang; Li, Yin; Wong, Sai-Wai; Zhang, Xiao; Wang, Shiyan; Fang, Liang; Gao, Qiang (Frontiers in Physics, 2022)
This work proposes a low-profile circularly polarized folded reflectarray antenna (CPFRA). Compared to traditional CPFRA that comprise the main reflectarray, a polarization grid (PG), and a linear-to-circular polarization (LP-CP) converter, the proposed CPFRA utilizes a polarization-sensitive LP-CP converter that plays the roles of both PG and LP-CP converter to minimize the CPFRA profile. One period of the polarization-sensitive LP-CP converter consists of an LP and a CP patch on the bottom and top layer of the substrates, respectively, which are connected by a metalized via. Due to its frequency-selective characteristic, the polarization-sensitive LP-CP surface can simultaneously reflect the x-polarized waves and transfer the received y-polarized waves into the CP state. A 1-bit unit cell at the bottom layer is adopted for polarization conversion and phase shift. A planar patch antenna is integrated as the primary feeding source. A high-gain circularly polarized folded reflectarray antenna at the X-band is designed, fabricated, and measured. Both simulated and measured results demonstrate the advantages of high gain and a lower profile of the proposed CPFRA compared to those in its traditional counterparts.